Coaxial μSAXS/POM simultaneous measurement for microstructural characterization of one-dimensional and two-dimensional crystalline polymer. (February 2022) - Fan, Yunyi; Liu, Guangfeng; Miao, Xiaran; Bian, Fenggang
Abstract: The microfocus beam small-angle X-ray scattering (μSAXS) provides a high spatial resolution ability, and the μSAXS/POM simultaneous measurement facilitates the acquisition of the micro-structural variations in the heterogeneous samples. Herein, at the SSRF BL19U2 beamline, a coaxial μSAXS/POM simultaneous measurement system has been established, comprising of the compound refractive lenses and an in-situ polarizing microscope. The SAXS beam size of 5.43 μm × 6.52 μm with a flux of 2.52 × 10 11 photons/s has been employed. In order to obtain realistic microstructural information, the visible light path of the polarizing microscope has been set coaxially with the X-ray to eliminate the field of view deviation. The microstructure of the ringed spherulites of the polyoxymethylene/polybutylenesuccinate blends and high-density polyethene (HDPE) fibers has been simultaneously characterized. The differences in the structural information at different positions inside the banded spherulites have been evaluated. The crystallinity of the HDPE fibers increases from the skin to core, whereas the average crystalline lamellae thickness of the HDPE fibers decreases from skin to core, and the long spacing remains almost unchanged in the fibers. Highlights: The establishment of coaxial μSAXS/POM simultaneous measurement. Realize the spatial structure characterization of one-dimensional and two-dimensional crystalline polymer on micron scale. Characterize the inner structure of the single ringed-spherulite. Characterize the differences in the structural information between the skin and core layers of single HDPE fiber, such as crystallinity, lamellae width and long period.